Potent broadly neutralizing antibodies mediate efficient antibody-dependent phagocytosis of HIV-infected cells. - Brian J Snow; Nida K Keles; Michael W Grunst; Sanath Kumar Janaka; Ryan T Behrens; David T Evans (PLoS Pathogens)
Antibody-dependent cellular phagocytosis (ADCP) has been implicated in protection against HIV-1. However, methods for measuring ADCP currently rely on the phagocytosis of gp120- or gp41-coated beads that do not reflect physiologically relevant conformations of the viral envelope glycoprotein or the size of a virus-infected cell. We therefore developed a novel approach for measuring ADCP of HIV-infected cells expressing natural conformations of Env. A monocytic cell line (THP-1 cells) or primary human monocytes were incubated with a CD4+ T cell line that expresses eGFP upon HIV-1 infection in the presence of antibodies and ADCP was measured as the accumulation of eGFP+ material by flow cytometry. The internalization of HIV-infected cells by monocytes was confirmed visually by image-capture flow cytometry. Cytoskeletal remodeling, pseudopod formation and phagocytosis were also observed by confocal microscopy. We found that potent broadly neutralizing antibodies (bnAbs), but not non-neutralizing antibodies (nnAbs), mediate efficient phagocytosis of cells infected with either primary or lab-adapted HIV-1. A nnAb to a CD4-inducible epitope of gp120 (A32) failed to enable ADCP of HIV-infected cells but mediated efficient phagocytosis of gp120-coated beads. Conversely, a bnAb specific to intact Env trimers (PGT145) mediated potent ADCP of HIV-infected cells but did not facilitate the uptake of gp120-coated beads. These results underscore the importance of measuring ADCP of HIV-infected cells expressing physiologically relevant conformations of Env and show that most antibodies that are capable of binding to Env trimers on virions to neutralize virus infectivity are also capable of binding to Env on the surface of virus-infected cells to mediate ADCP.